2000
DOI: 10.1074/jbc.m003278200
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Functional Domains of Nucleolar Protein B23

Abstract: Protein B23 is a multifunctional nucleolar protein whose cellular location and characteristics strongly suggest that it is a ribosome assembly factor. The protein has nucleic acid binding, ribonuclease, and molecular chaperone activities. To determine the contributions of unique polypeptide segments enriched in certain classes of amino acid residues to the respective activities, several constructs that produced N-and Cterminal deletion mutant proteins were prepared. The C-terminal quarter of the protein was sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
222
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(230 citation statements)
references
References 41 publications
8
222
0
Order By: Relevance
“…Structure-based discovery of small molecular inhibitors of NPM Nucleophosmin forms dimers and higher oligomers via its N-terminal globular domain (residues, 1-110) ( Figure 1a, Hingorani et al, 2000). We hypothesized that an SMI, targeting protein-protein interactions of the dimer interface would inhibit NPM function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structure-based discovery of small molecular inhibitors of NPM Nucleophosmin forms dimers and higher oligomers via its N-terminal globular domain (residues, 1-110) ( Figure 1a, Hingorani et al, 2000). We hypothesized that an SMI, targeting protein-protein interactions of the dimer interface would inhibit NPM function.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the discovery of several specific small molecular agents targeting anti-apoptotic targets such as Bcl-2-Bax (Oltersdorf et al, 2005), MDM2-p53 (Vassilev et al, 2004) and XIAP-SMAC (Oost et al, 2004). Under native condition, NPM exists as oligomers via its Nterminal molecular chaperone domain (Herrera et al, 1996;Hingorani et al, 2000;Namboodiri et al, 2004). We hypothesized that a specific SMI that disrupts the formation of oligomers would inhibit NPM function(s) in cancer cells.…”
Section: Apoptosis Induction By Npm Inhibitor Nsc348884 W Qi Et Almentioning
confidence: 99%
“…hnRNPU-B23 interaction is mediated by histone-binding domain of B23 and RNA-binding domain of hnRNPU Both B23 and hnRNPU were known to contain functional domains, which account for their distinctive biochemical functions (Hingorani et al, 2000;Kukalev Figure 1 B23 interacts with hnRNPA1 and hnRNPU in the cytosol on ActD treatment. (a) HeLa cells stably expressing GFP were treated with the 0.1% DMSO vehicle, CHX (25 mg/ml) and ActD (1 mg/ml), respectively, followed by immunostaining with anti-B23 antibody (red).…”
Section: B23 Binds To Hnrnpu and Hnrnpa1 In The Cytosol In Response Tmentioning
confidence: 99%
“…The multiple functions of B23 make it both a potential oncogene and a potential tumor suppressor, depending on expression levels and environmental stimuli (Grisendi et al, 2006). B23 possesses a nuclear-localization signal and a nuclearexport signal, which allows it to shuttle between nucleus and cytoplasm (Hingorani et al, 2000;Wang et al, 2005). The shuttling property of B23 contributes to its activity in various cellular processes including the transport of pre-ribosomal particles, the response to stress stimuli such as UV irradiation and hypoxia, as well as cell cycle regulation (Yung et al, 1985;Wu et al, 2002;Brady et al, 2004).…”
mentioning
confidence: 99%
“…Overexpression and tumorigenic activation of the Smoothened (SMO) protooncogene mediates c-myc overexpression, suggesting that SMO may also be a prognostic factor in HCC tumorigenesis (Sicklick et al, 2006). Nucleophosmin (NPM) is a major nucleolar phosphoprotein implicated in multiple cellular functions, including ribosomal protein assembly and transport (Verheggen et al, 2000;Huang et al, 2005), centrosome duplication (Okuda et al, 2000;Okuda, 2002;Grisendi et al, 2005), molecular chaperone activity in preventing protein aggregation (Hingorani et al, 2000;Szebeni et al, 2003), and regulating the activity of the tumour suppressors p53 (Colombo et al, 2002;Li et al, 2004;Maiguel et al, 2004) and p14 ARF (Itahana et al, 2003;Bertwistle et al, 2004;Brady et al, 2004). Earlier studies have shown that the level of NPM is markedly and promptly increased in association with cell commitment to mitogenesis (Feuerstein and Mond, 1987;Feuerstein et al, 1988).…”
mentioning
confidence: 99%